Efficacy and safety of ketoconazole combined with calmodulin inhibitor in solid organ transplantation: A systematic review and meta‐analysis. (30th September 2019) - Xue, Ting; Yang, Ting; Chen, Chaoyang; Wu, Songtao; Li, Min; Ma, Lingyun; Zhou, Ying; Cui, Yimin
Abstract: What is known and objective: Calcineurin inhibitors (CNIs) can significantly improve the results of solid organ transplantation regarding graft and patient survival. However, the high cost, chronic nephrotoxicity and other side effects are major challenges for the long‐term use of these drugs. Ketoconazole can significantly increase the plasma concentration of CNIs by inhibiting the activity of the cytochrome P450 enzyme. The combination of ketoconazole‐CNIs can reduce the cost of medication for patients by reducing the dosage of CNIs, but its safety is still controversial. Therefore, this study was designed to assess the safety and efficacy of this combination. Methods: We performed a systematic literature search in PubMed, Embase, Cochrane Library and clinicaltrials.gov for randomized controlled trials on ketoconazole and CNI (cyclosporin or tacrolimus) co‐administration in solid organ transplantation. Two authors independently selected studies, assessed the risk of bias and extracted data. The meta‐analysis was performed in RevMan 5.3 provided by the Cochrane Collaboration. PROSPERO registration number: CRD42019118796. Results and discussion: Five relevant trials with 326 patients were included. Compared with the controls, ketoconazole combined with CNIs can significantly reduce the dose of CNIs in patients receiving solid organ transplantation (WMD = −203.04 mg/day; 95% CI: −310.51 to −95.57, P  = .0002). There was no significant difference in serum creatinine between the experimental group and the control group (WMD = −0.19 mg/mL; 95% CI: −0.52 to 0.14, P  = .26). In addition, there was no significant difference in the number of rejections between the two groups (OR = 0.58; 95% CI: 0.27 to 1.22, P  = .15). What's new and conclusion: The co‐administration of ketoconazole and CNIs can significantly reduce the dose of CNIs. This combination may be safely used as a CNI‐sparing agent from the time of solid organ transplantation with low‐dose ketoconazole, based on the findings of this review. Abstract : Forest plot and meta‐analysis of the effect of ketoconazole group and control group on the dose of cyclosporine (mg/day) during follow‐up at 12 months.